2007
DOI: 10.1097/01.ccm.0000287588.69000.97
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local high mobility group box 1 concentrations during severe infection

Abstract: In severe sepsis, the kinetics of HMGB1 release may differ depending on the primary source of infection. In patients with severe infection, HMGB1 release may predominantly occur at the site of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 35 publications
5
39
2
Order By: Relevance
“…We previously demonstrated increased HMGB1 concentrations in BALF from the infected site of patients with pneumonia (van Zoelen et al, 2007), with S. pneumoniae being isolated in 3 out of 4 cases. Relative to healthy controls, mice with pneumonia induced by IAV had elevated HMGB1 levels in BALF at day 4 and day 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated increased HMGB1 concentrations in BALF from the infected site of patients with pneumonia (van Zoelen et al, 2007), with S. pneumoniae being isolated in 3 out of 4 cases. Relative to healthy controls, mice with pneumonia induced by IAV had elevated HMGB1 levels in BALF at day 4 and day 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that patients with peritonitis showed strongly elevated HMGB-1 concentrations in their abdominal fluid (5). Therefore, we here chose to administer HMGB-1 intraperitoneally to more closely mimic a possible clinical scenario of an (initially) localized infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dying of these mice paralleled the accumulation of systemic HMGB-1, and postponed treatment with an anti–HMGB-1 antibody protected against lethality caused by high-dose LPS administration or cecal ligation and puncture in mice (2, 3). Moreover, clinical observational studies have further implicated HMGB-1 as a late mediator of sepsis: patients with severe sepsis have elevated HMGB-1 concentrations in their circulation (2, 4, 5). In addition, we recently reported that patients with peritonitis have greater than 10-fold higher HMGB-1 concentrations in their abdominal fluid than in concurrently obtained plasma, suggesting that this mediator is released locally at the site of infection (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, HMGB-1 has been found to act as a "late" inflammatory cytokine that contributes to the pathological progression of sepsis and other inflammatory disorders (36). In patients with severe sepsis, the kinetic of circulating HMGB1 may differ from the classic mouse model findings depending on the primary source of infection (37). HMGB-1 has been proven to be a successful therapeutic target in experimental models of diverse infectious and inflammatory diseases (39).…”
Section: Discussionmentioning
confidence: 99%